Efficient Syntheses of (S)- and (R)-β-Proline - Chandra, Shambhu Deo; Fung, Ethan W. F.; Perrin, David M. (Synthesis, 2023)
A facile, efficient, and economical synthesis of both β-proline enantiomers starting from trans-4-hydroxy-l-proline is reported. Light-promoted radical Barton decarboxylation and nitrile introduction at C4 followed by hydrolysis gives the desired products in high optical purity. These routes should be of interest to those seeking economical access to β-proline for multiple applications.
Keywords: beta-proline; hydroxyproline; radical decarboxylation; organo-catalyst